Module Development with Problem Based Learning (PBL) Model Based on Environmental Wetland to Increase Students’ Learning Outcomes - Mohamad Nor Aufa; Rilia Iriani; Parham Saadi; Muhammad Hasbie; Muhammad Awaluddin Fitri; Amalia Yunita (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2020)
Research has been carried out on the development of modules with the Problem Based Learning (PBL) model based on wetland environments on the topic of acid-base solutions. This study aims to determine: the validity, practicality and effectiveness of module development. This study used a research & development design of a 4-D development model that was modified into 3-D, the data collection techniques used a test of student learning outcomes and a questionnaire. The research was conducted at SMAN 3 Banjarmasin with a sample of 10 students of class of XI PMIA 3 for small-scale trials, 24 students of XI PMIA 3 for limited-scale trials, and class of XI PMIA 1 and XI PMIA 2 with total 74 students for testing in a wide scale. Validity can be seen based on the results of the validation, the practicality of the students’ responses, and the effectiveness of the students' learning outcomes. The results showed that the module was considered valid with an average score of 146.4 and a percentage of 91.58% (very valid), practical with a percentage of 82.90% (good), effective with an average N-gain score of 0.84 (high), the average score of N-gain is 0.87 (high) for class of XI PMIA 1 and 0.86 (high) for class of XI PMIA 2. The results of this study indicate that the module with the Problem Based Learning (PBL) model based on the wetland environment on the topic of acid-base solutions is declared valid, practical and effective for use as a learning resource for students.